2024
DOI: 10.1177/07482337231224514
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment—based verification of the CertiPURTM limit values for toluene diamine and methylene dianiline in flexible polyurethane foam

Patrick de Kort,
Elke Jensen,
Mark W Spence
et al.

Abstract: Flexible polyurethane foams (PUF) are used in many consumer products. PUF may contain trace levels of aromatic diamine impurities that could represent a potential health risk. The risk associated with sleeping on a PUF mattress was evaluated. Toxicity benchmarks for sensitization and non-cancer endpoints were derived from the respective points-of-departure using standard assessment factors. For the cancer endpoints, toxicity benchmarks were derived from the 25th-percentile values of animal studies. Recently pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Polyurethanes (PUs) are among the most extensively used classes of polymers, most notably because of their tunable mechanical properties and utility as insulators . PUs are ubiquitous in domestic and industrial applications in the form of rigid and soft foams, coatings, adhesives, and elastomers. Despite their versatility, the disposal of PUs is unsustainable as most are landfilled or incinerated. , Conventional PU synthesis also raises environmental and health concerns associated with their hazardous isocyanate-containing monomers. Covalent adaptable networks (CANs) are promising for recycling PU waste and could reduce the demand for new monomer feedstocks. However, integrating new functional groups with dynamic bonds into commercial PUs is problematic as these monomers may not be readily applicable to application-relevant formulations and can compromise PU properties. Therefore, we introduce catalysts that promote bond exchange between carbamates themselves, such that commercially established PUs can be reprocessed without modifying their composition. , Recently, we demonstrated that carbamate exchange catalysts introduced into already-synthesized PU foam enabled their reprocessing into recycled films and foams. This method helps recycle existing PU waste, and the relevant exchange catalysts might also produce new PUs that can be reprocessed after use. Therefore, developing catalysts for both urethane formation and carbamate exchange can realize a more circular PU economy.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethanes (PUs) are among the most extensively used classes of polymers, most notably because of their tunable mechanical properties and utility as insulators . PUs are ubiquitous in domestic and industrial applications in the form of rigid and soft foams, coatings, adhesives, and elastomers. Despite their versatility, the disposal of PUs is unsustainable as most are landfilled or incinerated. , Conventional PU synthesis also raises environmental and health concerns associated with their hazardous isocyanate-containing monomers. Covalent adaptable networks (CANs) are promising for recycling PU waste and could reduce the demand for new monomer feedstocks. However, integrating new functional groups with dynamic bonds into commercial PUs is problematic as these monomers may not be readily applicable to application-relevant formulations and can compromise PU properties. Therefore, we introduce catalysts that promote bond exchange between carbamates themselves, such that commercially established PUs can be reprocessed without modifying their composition. , Recently, we demonstrated that carbamate exchange catalysts introduced into already-synthesized PU foam enabled their reprocessing into recycled films and foams. This method helps recycle existing PU waste, and the relevant exchange catalysts might also produce new PUs that can be reprocessed after use. Therefore, developing catalysts for both urethane formation and carbamate exchange can realize a more circular PU economy.…”
Section: Introductionmentioning
confidence: 99%